Analysis of Differences in Financial Performance Between Shari’a Banks and Conventional Banks In Indonesia - Anggitaningsih, Retna; Dono Hariyanto, Al Furqon (LPPM, Universitas Islam Syarifuddin Lumajang, 2023)
The focus of the government on banking deregulation was to facilitate banks operational activities and performance. Nevertheless, instances of violations persist, including, breaches of the minimum lending limit (BMPK), granting credit without a thorough feasibility study process, and non-compliance with liquidity reserve regulations. Even though there was rapid emergence of new banks, this expansion had not always corresponded to an improvement in the financial health of these institutions. The enactment of Law No. 10 of 1998 provided an opportunity for the establishment of anti-usury (credit interest) Islamic banks, which prompted existing conventional banks to adopt a dual banking system, as observed in Malaysia, Bahrain, Kuwait, and Indonesia. The growth of sharia banking holds the promise of fostering a stronger national banking sector. However, certain unresolved issues persist, particularly in assessing the performance disparity between shari’a and conventional banks. This study aimed to investigate the differences in the financial performance of both shari’a and conventional banks in Indonesia during the specified year (2021). It encompassed the population of conventional national private commercial banks and national private shari’a commercial banks. From this population, a sample of eight conventional and five shari’a banks that remained operational until 2021 was selected. The results showed three significant differences in the average financial performance between both banks, specifically, ROA, BOPO, and LDR. Conventional banks exhibited a comparatively lower ROA, higher BOPO, and lower LDR. Furthermore, the comprehensive financial performance analysis effectively distinguished between these two groups of banks. Regarding ROA, BOPO, and LDR, conventional banks appeared to be less profitable than shari’a banks, except in terms of CAR and RORA performance.